Assistance in Creating a Reading Corner as an Effort to Improve the Literacy Culture of Students at Bayung Gede Public Elementary School - Marina, Ni Ketut; Sudirman, I Nyoman (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Literacy skills are a crucial foundation for the academic development of elementary school students. However, the limited literacy facilities in rural schools, such as at Bayung Gede Public Elementary School, have led to a low interest in reading among students. This community service activity aims to assist the school in establishing a reading corner as a means to enhance the literacy culture. The implementation method used a participatory approach over three months (August–October 2025), involving teachers and fifth-grade students in the planning, creation, utilization, and evaluation of the reading corner. The results of the activity showed an increase in students' reading interest, evidenced by the growing habit of reading outside class hours, active participation in class discussions, and enthusiasm for bringing extra books from home. Teachers also became more creative in integrating the reading corner into daily literacy activities. Therefore, the assistance in creating the reading corner proved effective in fostering a literacy culture in elementary schools. This program can be replicated in other schools, especially in rural areas with limited facilities, as an effort to expand the school literacy movement.